2017
DOI: 10.1016/j.addbeh.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of fentanyl-contaminated heroin exposure among young adults who use prescription opioids non-medically

Abstract: Background The rate of overdose deaths caused by fentanyl-contaminated heroin (FCH) use is increasing rapidly in the United States. We examined risk factors for exposure to FCH and experiences with FCH use among young adult non-medical prescription opioids (NMPO) users. Methods We analyzed data from the Rhode Island Young Adult Prescription Drug Study (RAPiDS), which enrolled young adults aged 18 to 29 reporting prior 30 day NMPO use between January 2015 and February 2016. Participants completed questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 14 publications
(14 reference statements)
3
69
1
Order By: Relevance
“…Heroin users in Rhode Island are encountering illicitly made fentanyl and fentanyl analogs produced in clandestine labs, not the medical-grade drug (Mercado-Crespo et al, 2014). There is some evidence that chronic users of illicit or diverted opioids may prefer the physical effects of fentanyl to those of pure heroin (Comer, Sullivan, Whittington, Vosburg, & Kowalczyk, 2008; Greenwald, 2008), and may seek it out (Macmadu et al, 2017); however, with no drug quality information available to opioid consumers and a high local prevalence of fentanyl-related overdose, perceived desirability of fentanyl in Rhode Island currently appears low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heroin users in Rhode Island are encountering illicitly made fentanyl and fentanyl analogs produced in clandestine labs, not the medical-grade drug (Mercado-Crespo et al, 2014). There is some evidence that chronic users of illicit or diverted opioids may prefer the physical effects of fentanyl to those of pure heroin (Comer, Sullivan, Whittington, Vosburg, & Kowalczyk, 2008; Greenwald, 2008), and may seek it out (Macmadu et al, 2017); however, with no drug quality information available to opioid consumers and a high local prevalence of fentanyl-related overdose, perceived desirability of fentanyl in Rhode Island currently appears low.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study among young adults in the state who use prescription opioids non-medically found that 11% reported known or suspected fentanyl exposure through contaminated drugs in the past six months (Macmadu, Carroll, Hadland, Green, & Marshall, 2017), indicating that fentanyl is reaching a wide spectrum of opioid users in the region. However, without more knowledge about the local drug market and drug use behaviors in the context of pervasive fentanyl exposure, policy-makers are limited in their ability to identify andtarget the individuals at the greatest risk of overdose.…”
Section: Introductionmentioning
confidence: 99%
“…People who use opioids may prefer to use fentanyl as it is highly lipid-soluble, thus rapid-acting, and 40 times more potent at the opioid receptor than heroin, which results in fast onset euphoria and pain relief. Many PWID describe the experience as like heroin, but more intense (Amlani et al, 2015; Ciccarone, Ondocsin, & Mars, 2017; Macmadu, Carroll, Hadland, Green, & Marshall, 2017). Like heroin, fentanyl has a half-life of approximately 3-7 hours (Trescot, Datta, Lee, & Hansen, 2008), however, the duration of action of fentanyl is briefer, only 30-60 minutes for an intravenous injection, compared to 4-5 hours for heroin.…”
Section: Introductionmentioning
confidence: 99%
“…Department of Justice Drug Enforcement Admnistration, 2017), fentanyl and its analogs are visually indiscernible from one another, making it difficult to detect differences between them without thorough laboratory testing (Suzuki & El-Haddad, 2017). Persons who use drugs (PWUD) are often unaware when drugs are “cut”, or mixed with fentanyl (Carroll, Marshall, Rich, & Green, 2017; Macmadu, Carroll, Hadland, Green, & Marshall, 2017; Mars, Ondocsin, & Ciccarone, 2017; Spies et al, 2016; Stogner, 2014). Consequently, use of drugs containing fentanyl have been linked to sharp increases in rates of opioid morbidity and mortality (Centers for Disease Control & Prevention, 2017; Daniulaityte et al, 2017; Katz, 2017; Marshall et al, 2017; O’Donnell, Halpin, Mattson, Goldberger, & Gladden, 2017; Rudd, Aleshire, Zibbell, & Gladden, 2016; Rudd, Seth, David, & Scholl, 2016; Slavova et al, 2017).…”
Section: Introductionmentioning
confidence: 99%